2022
DOI: 10.1001/jamanetworkopen.2022.20969
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Effectiveness of Diversion of Cerebrospinal Fluid for Children With Severe Traumatic Brain Injury

Abstract: Key Points Question Is cerebrospinal fluid (CSF) diversion associated with improved outcomes or intracranial pressure in children with severe traumatic brain injury (TBI)? Findings In this comparative effectiveness study of 1000 children with severe TBI, there was no association between CSF diversion and Glasgow Outcome Score–Extended for Pediatrics at 6 months after injury in propensity-matched participants. However, CSF diversion was associated with decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…They found that there was no significant difference in GOS-EP between groups at 6 months but that the patients who received EVD had lower ICP during their acute care. 1 Bell et al 1 conclude that use of ventriculostomy drainage as a front-line treatment should be reconsidered. This is the largest study, to our knowledge, to look closely and specifically at the efficacy of EVD in children with severe TBI, from a multisite, international network that has shown admirable success in collecting large amounts of data in children with TBI who undergo ICP monitoring.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They found that there was no significant difference in GOS-EP between groups at 6 months but that the patients who received EVD had lower ICP during their acute care. 1 Bell et al 1 conclude that use of ventriculostomy drainage as a front-line treatment should be reconsidered. This is the largest study, to our knowledge, to look closely and specifically at the efficacy of EVD in children with severe TBI, from a multisite, international network that has shown admirable success in collecting large amounts of data in children with TBI who undergo ICP monitoring.…”
mentioning
confidence: 99%
“…Choice of parenchymal monitor vs ventriculostomy was not randomized in the study by Bell et al, 1 and the authors acknowledge at the outset that significant variability exists with respect to practice. The inclusion of centers spanning 8 countries and 5 continents ensures heterogeneity with respect to patient population, local resources, and individual practitioner approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Original Investigation titled “Comparative Effectiveness of Diversion of Cerebrospinal Fluid for Children With Severe Traumatic Brain Injury,” published July 8, 2022, there were errors in the Results sections of the Abstract and the main text. In the Abstract, the median (IQR) Glasgow Outcome Score–Extended for Pediatrics should have been 0 (−2 to 3) ( P = .40) and the mean (SD) difference in intracranial pressure should have been 3.98 (0.14) mm HG.…”
mentioning
confidence: 99%
“…In the main text, the P value for the propensity-matched analysis of odds ratio of death at 28 days should have been P = .62. This article has been corrected …”
mentioning
confidence: 99%